An automated underground space monitoring and communication system based on wireless sensor networks - Moridi, Mohammad Ali; Sharifzadeh, Mostafa; Jang, Hyong Doo; Kawamura, Youhei (Springer, 2019)
In the challenging environment and cutting-edge technology in mining industry, reliable and effective communication is a high-stake issue, along with the objectives of safe and efficient underground mining operations. Automation through remote and automatic systems has delivered improvements in workplace health and safety for employees, operational management, energy and cost-effectiveness, and real-time response to events. In this context, Wireless Sensor Networks (WSNs) have been widely employed in underground monitoring and communication systems for the purpose of environmental monitoring, the positioning of workers and equipment, operational monitoring and communication system. Considering the capabilities of WSNs, a ZigBee network is adopted in this study. The aim of this study is to propose a reliable and effective monitoring and communication system in underground environments, using WSN nodes were developed to sense environmental attributes and texting emergency messages. A trigger action plan for monitored attributes above normal and threshold value limits is programmed in the surface GIS management server. The system will provide multi-users surface operation and 3D visualization for realistic understanding of underground environment and miners’ conditions.